Das Umland Teurnias vo 2. Jahrhundert v. Chr. bis ins 1. Jahrhundert n.Chr: Eine Studie zur Siedlungskontinuität von der Latene- zur Romerzeit im oberen Drautal - Gugl, Christian (Arheološki vestnik, 2001)
A historically very important region of upper Carinthia, Lurnfeld, is also highly suitable for settlement oriented archaeological research. The central place is held by Holzer Berg (Teurnia) at the crossing point of two important roads. Changes in the settlement situation are indicated for this period: on one side, new bivalent areas (Teurnia), and on the other, new settlements (Faschendorf, Baldendorf). We have no true insight into the genesis of the settlement at Teurnia, which led to the construction of a lower town in the years from ca. AD 40/50 to 70/80. Most likely significant construction took place then, which can best be seen in the lower town.